2019
DOI: 10.3390/ijerph17010163
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tourists’ Experience of Quality of Street Foods on Destination’s Image, Life Satisfaction, and Word of Mouth: The Moderating Impact of Food Neophobia

Abstract: Due to growing food-related tourism, there is increasing interest about street foods worldwide, including South Korea. Many types of food-related experiences have been considered as one of the significant elements to develop positive perceptions about a destination, and street food has been recognized as a critical clue for encouraging tourists to a destination. Previous scholars mentioned street food as a public health risk element as well as a significant factor to attract tourists’ attention. Therefore, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 81 publications
(203 reference statements)
1
25
0
Order By: Relevance
“…The measurement items for the research factors used in this research were adopted from the existing studies [ 11 , 12 , 16 , 17 , 29 , 48 , 49 ] and adjusted to be appropriate to the current study context. All items were measured by a seven-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement items for the research factors used in this research were adopted from the existing studies [ 11 , 12 , 16 , 17 , 29 , 48 , 49 ] and adjusted to be appropriate to the current study context. All items were measured by a seven-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Image has long been believed a crucial dimension when explaining patrons’ decision-making procedures and attitudes of consumption [ 17 , 18 , 39 , 40 ]. Image refers to patrons’ overall perception of a firm and its product(s) based on the relations held in their memory [ 41 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from the perspective of food tourism, food culture is a tourist attraction that helps tourists understand the local culture through local foods and a unique dining environment and atmosphere. For tourists, the ultimate goal of touring a place is to feel content and thus to have positive behavioural and revisit intentions in the future and even to promote the destination to other people by word of mouth [ 4 , 5 , 39 ]. Therefore, when promoting Taiwanese street food to food tourists, it is recommended that the use of rational appeal be reduced or even avoided; instead, emotional methods that emphasize pictures, stories, emotions and cultural experiences should be adopted to help foreigners reduce their fear and uncertainty regarding certain Taiwanese delicacies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Lee et al [ 39 ] demonstrated the profound effect of food neophilia/neophobia on predicting consumers’ willingness to try unfamiliar foods. Henriques et al [ 40 ] also confirmed that food neophilia/neophobia affects consumers’ preference for novel foods and can be used to predict their acceptance of such foods.…”
Section: Literature Reviewmentioning
confidence: 99%